The Island of Gorée, a UNESCO world heritage site: contradictory memories of a classified and inhabited place. - (:unkn) unknown (My University, 2009)
Heritage from colonial times related to transatlantic slavery gave birth to a specific cultural tourism in Sub-Saharan Africa. The Island of Gorée in Senegal, a UNESCO world heritage site since 1978, has become an essential tourist destination – the first one in the country – and a symbol with a strong postcolonial identity that drives huge media attention. As for other historical emblems in Sub-Saharan Africa, the past of the Island of Gorée has been both inherited and rebuilt, and lies at the core of many political and cultural debates. As a district Community since 1996, this memorial site is also an inhabited place which is daily used and perceived in many different ways, as various actors move, live and work on this island. Several social, economic and political issues arise from its classification: they unveil differing definitions of this world heritage site, which question its cultural and historical specificity or shape other social imaginaries. The tourist gaze can frame memorial presentations, but the way they are challenged or rejected at a local scale results in social dynamics which are essential to the political and economic analysis of multidimensional heritage.
Keywords: African Research